MicroRNA-34a: Potent Tumor Suppressor, Cancer Stem Cell Inhibitor, and Potential Anticancer Therapeutic - Li, Wen (Jess); Wang, Yunfei; Liu, Ruifang; Kasinski, Andrea L.; Shen, Haifa; Slack, Frank J.; Tang, Dean G. (Frontiers in Cell and Developmental Biology, 2021)
Overwhelming evidence indicates that virtually all treatment-naïve tumors contain a subpopulation of cancer cells that possess some stem cell traits and properties and are operationally defined as cancer cell stem cells (CSCs). CSCs manifest inherent heterogeneity in that they may exist in an epithelial and proliferative state or a mesenchymal non-proliferative and invasive state. Spontaneous tumor progression, therapeutic treatments, and (epi)genetic mutations may also induce plasticity in non-CSCs and reprogram them into stem-like cancer cells. Intrinsic cancer cell heterogeneity and induced cancer cell plasticity, constantly and dynamically, generate a pool of CSC subpopulations with v¬arying levels of epigenomic stability and stemness. Despite the dynamic and transient nature of CSCs, they play fundamental roles in mediating therapy resistance and tumor relapse. It is now clear that the stemness of CSCs is coordinately regulated by genetic factors and epigenetic mechanisms. Here, in this Perspective, we first provide a brief updated overview of CSCs. We then focus on miR-34a, a tumor-suppressive microRNA (miRNA) devoid in many CSCs and advanced tumors. Being a member of the miR-34 family, miR-34a was identified as a p53 target in 2007. It is a bona fide tumor suppressor, and its expression is dysregulated and downregulated in various human cancers. By targeting stemness factors such as NOTCH, MYC, BCL-2 and CD44, miR-34a epigenetically and negatively regulates the functional properties of CSCs. We shall briefly discuss potential reasons behind the failure of the first-in-class clinical trial of MRX34, a liposomal miR-34a mimic. Finally, we offer several clinical settings where miR-34a can potentially be deployed to therapeutically target CSCs, and advanced, therapy-resistant and p53-mutant tumors in order to overcome therapy resistance and curb tumor relapse.